2010
DOI: 10.1177/000348941011900801
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of the Digisonic SP Cochlear Implant Fixation System with Titanium Screws in 156 Patients

Abstract: The fixation system with screws embedded in the Digisonic SP involves a fast and simple surgical technique that seems to efficiently prevent implant migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
(30 reference statements)
0
25
0
1
Order By: Relevance
“…The receiver is similar to the monaural Digisonic SP device: the coil, magnet, and electronics are boxed in a single ceramic structure. The receiver fixation is assured by two titanium screws, without drilling a bony well [Guevara et al, 2010]. Each electrode array comprises twelve active electrodes along an 18-mm active length, with an associated extra-cochlear ground electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The receiver is similar to the monaural Digisonic SP device: the coil, magnet, and electronics are boxed in a single ceramic structure. The receiver fixation is assured by two titanium screws, without drilling a bony well [Guevara et al, 2010]. Each electrode array comprises twelve active electrodes along an 18-mm active length, with an associated extra-cochlear ground electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The Digisonic SP (MXM -Neurelec, Vallauris, France) implant was introduced in 2004 and has a similar basic layout to other currently available commercial devices, with a ceramic/titanium internal receiver package and an external ear-level speech processor [13]. Highly positive outcomes with this device have been reported in unilaterally implanted adults [14,15], but outcomes in children and, in particular, with bilateral devices have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, authors have reported experiences similar to ours with revision surgery using the subperiosteal pocket technique (6,8). In this technique, drilling is unnecessary to create a bone bed for the IRS and electrodes.…”
Section: Resultsmentioning
confidence: 61%